Das Geschenk eines Rhapsoden: Über eine Weihinschrift aus Dodona - Pozdnev, Michael (Hyperboreus, 2017)
The inscription on the rim of a small tripod found during the excavations in the sanctuary of Dodona in 1878, reads: ‘Terpsicles, the rhapsode, dedicated this to Zeus Naios’. It is dated by C. Carapanos and A. Kirchhoff into the 5th cent. BC, and can thus be considered the earliest non-literary source on the Homeric rhapsodes. It also served as a proof that the musical festivals were carried on at Dodona as early as the Classical age. However, no winner should necessarily dedicate his prize at the place where he had won it. The evidence proves just the contrary: Hesiod dedicated his tripod, which he won at Chalcis, to the Muses of Helicon, and the inscriptions of the winners at the Naia festival celebrated at Dodona since the Hellenistic age are all found elsewhere. Whether Terpsicles competed at Dodona or at some other place better known for its connection with rhapsodic performances, it should be answered why he chose this particular sanctuary, far from his homeland (since he probably was a Milesian), as the most suitable for his donation. The attractiveness of Dodona for rhapsodic offerings might be further conﬁrmed by another votive inscription, that of Klearchos, previously not discussed in the Dodonian context because of its uncertain provenance. What was it, then, that made the Homeric reciters dedicate their awards to the Zeus Naios of Dodona? Their ‘concert program’ certainly included the Patrocleia and hence the prayer of Achilles to Ζεὺς Δωδωναῖος. The masterly recitation of this scene could bring them victory. Moreover, the Athenian tragedy reﬂected the revival of interest in Dodona, caused presumably by the establishment of the cult of Dione and the cult of Zeus Naios. Consequently, the rhapsodes gladly included the prayer of Achilles in their repertoire, and won prizes which they dedicated to the deity whom they also prayed to.